Association between energy and protein adequacy with quality of life in mechanically ventilated critically ill patients: a preliminary result - Tah, PC; Vineya-Rai, HR; Poh, BK; Mat Nor, Mohd Basri; A.M., Hazreen; Kee, CC; K.Z., Mazuin; Z.Y., Lee; H., Mohd Shahnaz (Elsevier Inc, 2018)
Rationale: There is limited clinical research investigating nutritional adequacy on quality of life (QoL) among survivors in critical care. Methods: This is a prospective observational cohort study conducted among mechanically ventilated critically ill patients. Energy requirements were estimated by Indirect Calorimetry and protein requirements were estimated by 24-h urinary urea. Nutritional intake was recorded daily until death, discharge, or until 14th evaluable day. Eight domains of QoL were assessed by validated SF-36(v2) at six months post-ICU admission. Association between two groups (<70% and ≥70% of energy and protein requirement) with QoL was examined using logistic regression with adjustment for potential confounders. Results: This study aims to determine the association between energy and protein adequacy with QoL among critically ill patients. Of 154 patients, 71 patients (46.1%) were alive, 69 patients (44.8%) died and 14 patients (9.1%) gave no response at 6 months followup. Patient characteristics at follow-up: age 50.6±19.6 years; 62.0% male; body mass index 24.9 (22.3–28.7) kg/m2; APACHE II score 21.2±5.2. Mean QoL score was 58.6±15.9, with scores ≥53 indicating better QoL. Results showed patients with protein, but not energy, adequacy of ≥70% had potential trend towards better QoL though not statistically significant (adjusted OR 2.62; 95%CI 0.80- 8.53; p=0.11). Protein adequacy ≥70% significantly improved bodily pain status (p<0.05), but no significant difference was found in seven other domains of QoL. Conclusion: This preliminary result suggest higher protein adequacy improve Bodily Pain status and may potentially lead towards better overall QoL. We opine that earlier nutrition intervention may assist in improving QoL but needs further investigation.